2022
DOI: 10.1093/ofid/ofac048
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Success After Periprosthetic Joint Infection: 24-Month Follow up From a Multicenter Prospective Observational Cohort Study of 653 Patients

Abstract: Background Peri-prosthetic joint infection (PJI) is a devastating condition and there is a lack of evidence to guide its management. We hypothesised that treatment success is independently associated with modifiable variables in surgical and antibiotic management. Methods Prospective, observational study at 27 hospitals across Australia and New Zealand. Newly diagnosed large joint PJIs were eligible. Data were collected at ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Second, PJI is a complex disease process and therefore no standardized treatment protocol has been defined to date 45 . As such, patients at the same institution may have received different management plans 46 . This may have confounded our analysis and may have reduced the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PJI is a complex disease process and therefore no standardized treatment protocol has been defined to date 45 . As such, patients at the same institution may have received different management plans 46 . This may have confounded our analysis and may have reduced the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Prosthetic joint infection (PJI) is a devastating complication of joint arthroplasty that is associated with significant patient morbidity and economic burden (Del Pozo and Patel, 2009;Moore et al, 2015). PJI complicates 1 %-2 % of primary arthroplasties (Del Pozo and Patel, 2009) and up to 8 % of cases following revision arthroplasty (Quinlan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prosthetic joint infection (PJI) is a devastating complication of joint arthroplasty that is associated with significant patient morbidity and economic burden (Del Pozo and Patel, 2009;Moore et al, 2015). PJI complicates 1 %-2 % of primary arthroplasties (Del Pozo and Patel, 2009) and up to 8 % of cases following revision arthroplasty (Quinlan et al, 2020). Identification of pathogenic organisms from culture of synovial fluid and periprosthetic tissue is a cornerstone of PJI diagnosis and treatment decisions (Parvizi et al, 2018;McNally et al, 2021;Osmon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors may have contributed to this, including the varying microbiological profiles and PJI type between each group. Other studies reporting treatment success include Davis et al [ 39 ], who analysed 2-year outcome data of patients with large joint PJI and reported on clinical cure (defined as: alive, absence of clinical or microbiological evidence of infection, and not requiring ongoing antibiotic therapy), and treatment success which was defined as clinical cure (as above) plus index prosthesis still in situ. Based on these definitions, clinical cure rate was 69%, while 54% of patients had treatment success in this study, which appear quite low however this could be contributed to by how they variably defined treatment success.…”
Section: Discussionmentioning
confidence: 99%